2022
DOI: 10.1029/2021jg006552
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification and DNRA in Urban Accidental Wetlands in Phoenix, Arizona

Abstract: Nitrogen is an essential, often limiting, element for biological growth that can act as a pollutant if present at high concentrations. Excessive nitrogen in highly biologically available forms, especially nitrate (NO 3 − ), is common in urban ecosystems. Urban ecosystems tend to have higher NO 3 − burdens due to higher inputs from fertilizer application (Baker et al., 2001;Law et al., 2004), deposition from fossil fuel combustion (Bettez & Groffman, 2013;Hale et al., 2014), and treatment of sewage (Lauver & Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Unfortunately, our analysis did not include direct measurements of DNRA, which should be performed in the future as it is an understudied, potentially important component of riparian N cycling. Indeed, zones of concentrated ammonium-N have been observed in other riparian systems with similar groundwater hydrodynamics, such as beaver ponds (Duval & Hill, 2006;Lazar et al, 2015;Naiman et al, 1994) and urban "accidental" wetlands (Handler et al, 2022). While many early studies have typically attributed high ammonium-N concentrations to ammonification and suppression of nitrification, there is increasing appreciation of the importance of DNRA as a mechanism for N production in anoxic soils/sediments.…”
Section: Drivers Of (And Competitors To) Denitrificationmentioning
confidence: 98%
“…Unfortunately, our analysis did not include direct measurements of DNRA, which should be performed in the future as it is an understudied, potentially important component of riparian N cycling. Indeed, zones of concentrated ammonium-N have been observed in other riparian systems with similar groundwater hydrodynamics, such as beaver ponds (Duval & Hill, 2006;Lazar et al, 2015;Naiman et al, 1994) and urban "accidental" wetlands (Handler et al, 2022). While many early studies have typically attributed high ammonium-N concentrations to ammonification and suppression of nitrification, there is increasing appreciation of the importance of DNRA as a mechanism for N production in anoxic soils/sediments.…”
Section: Drivers Of (And Competitors To) Denitrificationmentioning
confidence: 98%
“…As Figure 3 shows, the soil ammonium concentration did not change significantly ( P > 0.05) between the beginning and end of the incubations, which indicated that dissimilatory nitrate reduction to ammonium (DNRA) was negligible. In addition, study showed that DNRA may be a minimal pathway at high nitrate concentrations ( Handler et al, 2022 ), it is generally believed that low nitrogen and high carbon will tilt the balance to DNRA ( Van Den Berg et al, 2016 ; Pandey et al, 2020 ; Wei et al, 2022 ), the opposite is the high nitrogen and lower carbon contents in this study. Denitrification was the main nitrate reduction pathway, the amount of nitrate consumed (65 μmol N) was significantly larger than the cumulative amount of the N 2 O plus N 2 (31 μmol N) produced by day 98 (Experiment 2).…”
Section: Resultsmentioning
confidence: 59%